A paramyxovirus-like model for Ebola virus bipartite promoters. - Irina Gutsche; Philippe le Mercier; Daniel Kolakofsky (PLoS Pathogens, 2020)
Paramyxo- and filovirus nucleocapsids (NCs) have bipartite promoters at their 3' ends to initiate RNA synthesis. The 2 elements, promoter element 1 (PE1) and promoter element 2 (PE2), are separated by a spacer region that must be exactly a multiple of 6 nucleotides (nt) long. Paramyxovirus NCs have 13 nucleoprotein (NP) subunits/turn, such that PE1 and PE2 are juxtaposed on the same face of the NC helix, for concerted recognition by the viral polymerase. Ebola virus (EBOV) NCs, in contrast, have 25 to 28 subunits/turn, meaning that PE1 and PE2 cannot be juxtaposed. However, there is evidence that the number of subunits/turn at the 3' end of the EBOV NC is variable. We propose a paramyxovirus-like model for EBOV explaining why there are 8 contiguous copies of the PE2 repeat when 3 are sufficient, why expanding this run to 13 further improves minigenome performance, and why there is a limit to the number of hexa-nt that can be inserted in the spacer region.